Direct versus indirect illumination of a prototype luminescent solar concentrator. (December 2015) - Debije, Michael G.; Rajkumar, Vikram A.
Highlights: Demonstrates relative performance increase in luminescent solar concentrators under cloudy conditions. Demonstrates relative performance increase in luminescent solar concentrators under low light conditions. Show advantage of attaching PV cells to lightguide edges with glue is dependent on the solar light conditions. Abstract: The luminescent solar concentrator could find application as an alternative way of generating electricity from sunlight in urban settings by virtue of its aesthetic and performance qualities. In particular, it has long been stated that the device functions equally well in direct and diffuse light, especially useful in the built environment but with little verification of this statement. In this work, we demonstrate the validity of this claim by comparing the performance of the luminescent solar concentrator in outdoor conditions ranging from clear to cloudy. We offer the explanation of an altered illumination spectrum to account for the increased efficiency of the device in overcast conditions. We also show the effect of gluing cells to the lightguide edge and conjecture on the differing impact the gluing has under direct and indirect sunlight.